PRESERVING TRADITIONS - M. V. Kharkevich (Vestnik MGIMO-Universiteta, 2017)
In the analyzed publication the author presents the various aspects of the development of scientific school at MGIMO-University. The author made a special emphasis on the “human” dimension on the disclosure of personal features of the heroes of memories, who were somehow connected with the Moscow State Institute of International Relations. The details that can only be accessed by a direct participant in the events and that allow the reader to plunge into the social context of what was happening are of great significance. The review concludes that the undoubted literary merits of the product complement the deeper content of the book.